Holocene atmospheric circulation in the central North Pacific: a new terrestrial diatom and δ18O dataset from the Aleutian Islands - Bailey, Hannah L.; Kaufman, Darrell S.; Sloane, Hilary J.; Hubbard, Alun L.; Henderson, Andrew C.G.; Leng, Melanie J.; Meyer, Hanno; Welker, Jeffrey M. (Elsevier, 2018)
The North Pacific is a zone of cyclogenesis that modulates synoptic-scale atmospheric circulation, yet there is a paucity of instrumental and paleoclimate data to fully constrain its long-term state and variability. We present the first Holocene oxygen isotope record (δ18Odiatom) from the Aleutian Islands, using siliceous diatoms preserved in Heart Lake on Adak Island (51.85° N, 176.69° W). This study builds on previous work demonstrating that Heart Lake sedimentary δ18Odiatom values record the δ18O signal of precipitation, and correlate significantly with atmospheric circulation indices over the past century. We apply this empirical relationship to interpret a new 9.6 ka δ18Odiatom record from the same lake, supported by diatom assemblage analysis. Our results demonstrate distinct shifts in the prevailing trajectory of storm systems that drove spatially heterogeneous patterns of moisture delivery and climate across the region. During the early-mid Holocene, a warmer/wetter climate prevailed due to a predominantly westerly Aleutian Low that enhanced advection of warm 18O-enriched Pacific moisture to Adak, and culminated in a δ18Odiatom maxima (33.3‰) at 7.6 ka during the Holocene Thermal Maximum. After 4.5 ka, relatively lower δ18Odiatom indicates cooler/drier conditions associated with enhanced northerly circulation that persisted into the 21st century. Our analysis is consistent with surface climate conditions inferred from a suite of terrestrial and marine climate-proxy records. This new Holocene dataset bridges the gap in an expanding regional network of paleoisotope studies, and provides a fresh assessment of the complex spatial patterns of Holocene climate across Beringia and the atmospheric forces driving them.